2021
DOI: 10.1002/dmrr.3509
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action and secretion independent of traditional risk factors predict new‐onset type 2 diabetes in Iraqi and Swedish born citizens – The MEDIM cohort study

Abstract: Aims Our aim was to study the incidence of type 2 diabetes in a population‐based cohort of Swedish and Iraqi born individuals, focussing on traditional risk factors, insulin action, insulin secretion and ethnicity. Materials and Methods The cohort consisted of 1164 Iraqi and 693 Swedish‐born citizens. We investigated the association between new‐onset type 2 diabetes and the predictors including lifestyle factors, metabolic risk markers, country of birth, insulin sensitivity and secretion assessed by Matsuda in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…24,25 Recent prospective epidemiological studies have highlighted the associational effect of LDL/HDL on the prediction of type 2 diabetes onset. 26 higher AUC and accuracy than logistic regression. 27…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…24,25 Recent prospective epidemiological studies have highlighted the associational effect of LDL/HDL on the prediction of type 2 diabetes onset. 26 higher AUC and accuracy than logistic regression. 27…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have found an inverse relationship between the levels of HDL‐C with 2hPG and type 2 diabetes incidence 24,25 . Recent prospective epidemiological studies have highlighted the associational effect of LDL/HDL on the prediction of type 2 diabetes onset 26 . These findings were consistent with our study results, wherein our model involving FPG, HbA1c, age, heart rate, ALT, TG, LDL‐C, SBP, BMI, and HDL‐C could diagnose IPH with higher sensitivity and specificity in a population with normal FPG.…”
Section: Discussionmentioning
confidence: 99%